2013
DOI: 10.1080/15387216.2014.908313
|View full text |Cite
|
Sign up to set email alerts
|

Is institutional trust related to pro-immigrant attitudes? A pan-European evidence

Abstract: This paper examines the factors that are related to attitudes toward immigrants in Europe, with a particular focus on the role of institutional trust in shaping these attitudes. We go one step further compated to previous studies by investigating separately two different groups of people -members of the ethnic majority and ethnic minority populations in European countries. We use data from the European Social Survey fifth round database for 25 countries. The results of the paper show that trust in institutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 29 publications
0
11
0
2
Order By: Relevance
“…Perceived threat is one of the key factors that links in-group favoritism to hostility toward out-groups (Brewer, 1999; Riek et al, 2006). Pride in the political institutions of the country indicates a certain level of trust in these institutions, which in turn is related to more positive attitudes toward immigrants (Halapuu et al, 2013). Political pride is also likely to contribute to a belief in a strong state that is able to protect its citizens, which can as well reduce perceptions of possible threats from the outsiders.…”
Section: National Identity and Anti-immigrant Attitudesmentioning
confidence: 99%
“…Perceived threat is one of the key factors that links in-group favoritism to hostility toward out-groups (Brewer, 1999; Riek et al, 2006). Pride in the political institutions of the country indicates a certain level of trust in these institutions, which in turn is related to more positive attitudes toward immigrants (Halapuu et al, 2013). Political pride is also likely to contribute to a belief in a strong state that is able to protect its citizens, which can as well reduce perceptions of possible threats from the outsiders.…”
Section: National Identity and Anti-immigrant Attitudesmentioning
confidence: 99%
“…In a cross-country analysis of 19 European countries, the authors find that higher levels of social trust are associated with positive attitudes towards immigration. Economidou et al (2017) and Halapuu et al (2013) also confirm that across Europe individuals with high social capital exhibit a more positive attitude toward immigration.…”
Section: Channels Of Own Schoolingmentioning
confidence: 90%
“…Generalized social trust is commonly defined as a general willingness to trust strangers, i.e., people we do not have any information about (Uslaner, 2002;Bahry et al, 2005). Institutional trust, on the other hand, rests upon people's perceptions of how well the social and organizational environment in a society operates (e.g., Miller, 1974;Williamson, 1993;Halapuu et al, 2013). Institutional trust can help to overcome the problems of collective action (Fukuyama, 1995;Putnam, 2000), and it has been shown that institutional trust helps improve native people's attitudes toward immigrants and minorities (Espenshade and Hempstead, 1996;Husfeldt, 2006;Halapuu et al, 2013).…”
Section: Background Literature Reviewmentioning
confidence: 99%
“…Institutional trust, on the other hand, rests upon people’s perceptions of how well the social and organizational environment in a society operates (e.g., Miller, 1974 ; Williamson, 1993 ; Halapuu et al, 2013 ). Institutional trust can help to overcome the problems of collective action ( Fukuyama, 1995 ; Putnam, 2000 ), and it has been shown that institutional trust helps improve native people’s attitudes toward immigrants and minorities ( Espenshade and Hempstead, 1996 ; Husfeldt, 2006 ; Halapuu et al, 2013 ). Likewise, institutional trust could also shape immigrants’ willingness to cooperate with people and organizations in the host country, which could have an impact on their propensity to participate in social interactions and the labor market.…”
Section: Introductionmentioning
confidence: 99%